2003
DOI: 10.1016/j.curtheres.2003.09.003
|View full text |Cite
|
Sign up to set email alerts
|

Effects of pyrimethamine versus proguanil in malarial chemoprophylaxis in children with sickle cell disease: a randomized, placebo-controlled, open-label study

Abstract: Background: Malarial chemoprophylaxis is essential for patients with homozygous sickle cell disease (SCD) who live in areas where malaria is endemic. Endemic regions include most sub-Saharan African countries and Southeast Asia.Objective: This study compared the efficacy and tolerability of pyrimethamine with that of proguanil and placebo in the prevention of malaria and the complications of Plasmodium falciparum infection (hepatomegaly, splenomegaly, bone pain crisis, hemolytic crisis) in children with SCD.Me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 17 publications
0
24
0
Order By: Relevance
“…58,59,61,65 Also, studies on the antiplatelet agent ticlopidine, the dietary supplement zinc, and antimalarial prophylaxis for patients in malaria-endemic regions provided encouraging results. 50,55,70 However, 23 of the 36 studies included in this review did not show any beneficial effect of the intervention under investigation. 38,40,43,[46][47][48][49][51][52][53][54]57,60,62,63,[66][67][68][69][71][72][73][74] The other studies were either too small or methodologically inadequate to draw strong conclusions.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…58,59,61,65 Also, studies on the antiplatelet agent ticlopidine, the dietary supplement zinc, and antimalarial prophylaxis for patients in malaria-endemic regions provided encouraging results. 50,55,70 However, 23 of the 36 studies included in this review did not show any beneficial effect of the intervention under investigation. 38,40,43,[46][47][48][49][51][52][53][54]57,60,62,63,[66][67][68][69][71][72][73][74] The other studies were either too small or methodologically inadequate to draw strong conclusions.…”
Section: Discussionmentioning
confidence: 99%
“…Malaria infections are an important trigger for VOCs in SCD. In the open-label, placebo-controlled study by Eke et al, 70 a significantly lower proportion of patients with VOCs was observed in the proguanil arm, along with a lower proportion of patients with hospitalizations in the pyrimethamine arm as compared with placebo (Table 1). In the study by Diop et al, 69 monthly sulfadoxinepyrimethamine treatment as compared with placebo during hightransmission malaria season did not affect the frequency of VOCs or hospitalizations.…”
Section: Quality Of the Included Studiesmentioning
confidence: 99%
See 3 more Smart Citations